ChemInform Abstract: Synthesis and Antiviral Activity of New Substituted Methyl [2‐(Arylmethylene‐hydrazino)‐4‐oxo‐thiazolidin‐5‐ylidene]acetates. Issue 51 (17th December 2013) - Saeed, Aamer; Al‐Masoudi, Najim A.; Latif, Muhammad
Abstract The title compounds (III) are obtained by cyclocondensation of thiosemicarbazones (I) with but‐2‐ynedioate (II) under solvent‐free microwave irradiation conditions.